Gale directory of databases. - Gale Research Inc.; Gale Group (Detroit Gale Research, 1997)
This is a guide to computer-readable databases available online, in CD-ROM format, or in other magnetic formats. Details include database descriptions, costs, and whom to contact for purchase. The material is indexed alphabetically, and by subject, vendor, and producer.
Published: Detroit : Gale Group, 1999-
Also available electronically through the online services: Data-Star, ORBIT Search Service, and Questel.
Latest issue consulted: 30th ed., published in 2008.
Issued in 2 volumes: v. 1, Online databases, and: v. 2, CD-ROM, diskette, magnetic tape, handheld, and batch access database products.
Issues for <2001>-2005 called <2001, pt. 1>-2005, pt. 2.
Vols. published 2008- called 30th ed.- and lack cover date.
Keywords: Databases -- Directories